Pengembangan Ekonomi Desa dalam Islam: Penerapan Sharia Value di Pasar Tradisional - Sriani, Endang (Universitas Islam Negeri Sunan Kudus, 2020)
This study aims to determine how the implementation of trade activities and the aplication of Islamic Sharia Values at az-Zaitun Sharia market and to know the efforts of it in realizing of local economic independence. A qualitative approach wa employed in this field research, the data collection techniques include observation and interview with the sellers and the founder of az-Zahra sharia market. The results of this study indicate that, firstly, the establishment of az-Zaitun sharia market aims to protect the consumers and to create an equitable price. Secondly, the sellers has implemented 8 concept formulated by the founder, but there have some obstacles. It is caused by the exixtence of illegal market around az-Zaitun. Thirdly, az-Zaitun sharia market can bedeveloped to realize a local economic independence by making the market as a product wondow for the communities.